Comparative tidal analysis using Admiralty and Least Square methods at Tanjung Perak Port, Surabaya, Indonesia - Calista, Tsabitah Nandiantara; Nadar, Harman; Sawiji, Asri; Fahmi, Muhammad Yunan (UIN Sunan Ampel Surabaya, 2025)
This study evaluates tidal predictions using the Admiralty and Least Square methods by comparing their performance against real-time measurement and prediction data at Tanjung Perak Port, Surabaya, East Java. The analysis focuses on differences in harmonic components, tidal classifications, and tidal elevations. Results reveal a shift in Formzahl values from Mixed Tide, Prevailing Semidiurnal (1.494) in real-time data to Mixed Tide, Prevailing Diurnal (1.922) in prediction data, primarily due to variations in the amplitude of diurnal and semi-diurnal constituents. High correlation coefficients and low RMSE values demonstrate that both methods are suitable for tidal forecasting, with the Least Square method offering more refined long-term analysis and the Admiralty method showing greater efficiency in short-term tidal calculations. These findings contribute to improved maritime operations, coastal management, and sediment transport modeling, and highlight the importance of continued validation and methodological refinement to enhance predictive accuracy.